Analisis Kualitas Website Perpustakaan Menggunakan Metode Webqual 4.0 - Mahida Hanifah Rahmadini; Asif Faroqi; Anita Wulansari (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
The emergence of several technical problems related to the availability of adequate functional features, led to the need for an analysis of the website performance of the UPT "Veteran" East Java Library, so that the website's performance was in line with user expectations. This research analyzes the website of the UPN "Veteran" East Java Library UPT website using the Webqual 4.0 method, aiming to find out the website indicators that need to be maintained and improved performance. The analysis is carried out referring to the Usability, Information Quality, and Service Interaction Quality parameters, where each parameter consists of indicators. The sampling technique used is proportionate stratified random sampling, with website users as respondents. The method of data collection is in the form of distributing questionnaires. The data were analyzed using the Importance-Performance Analysis method. The results showed that the overall performance of the UPT "Veteran" East Java Library website was sufficient to meet user expectations. However, it was found several indicators that need to be improved by the website manager, namely: ease of understanding website navigation, attractiveness of Website appearance, and the availability of information on websites that are easy to understand.Keywords: Performance; Importance-Performance Analysis; Usability; Information Quality; Service Interaction Quality Abstrak. Munculnya beberapa permasalahan teknis yang berkaitan dengan ketersediaan operasi fitur-fitur fungsional secara memadai, menyebabkan perlunya dilakukan analisis kinerja website UPT Perpustakaan UPN “Veteran” Jawa Timur, agar kinerja website sesuai harapan pengguna. Peneltian ini menganalisis website UPT Perpustakaan UPN “Veteran” Jawa Timur menggunakan metode Webqual 4.0., bertujuan mengetahui indikator website yang perlu dipertahankan dan ditingkatkan kinerjanya. Analisis dilakukan mengacu pada parameter Usability, Information Quality, dan Service Intteraction Quality, dimana setiap parameter terdiri atas indikator. Teknik sampling yang digunakan adalah proportionate stratified random sampling, dengan responden pengguna website. Metode pengumpulan data berupa penyebaran kuesioner. Data dianalisis menggunakan metode Importance-Performance Analysis. Hasil penelitian menunjukkan secara keseluruhan kinerja website UPT Perpustakaan UPN “Veteran” Jawa Timur sudah cukup memenuhi harapan pengguna. Namun ditemukan beberapa indikator yang perlu ditingkatkan kinerjanya oleh pihak pengelola website yaitu: kemudahan memahami Navigasi website, kemenarikan tampilan website, serta ketersediaan informasi pada website yang mudah dimengerti.Kata kunci: Kinerja; Importance-Performance Analysis; Usability; Information Quality; Service Intteraction Quality